Correlations Between the Metabolome and the Endophytic Fungal Metagenome Suggests Importance of Various Metabolite Classes in Community Assembly in Horseradish (Armoracia rusticana, Brassicaceae) Roots - Plaszkó, Tamás; Szűcs, Zsolt; Cziáky, Zoltán; Ács-Szabó, Lajos; Csoma, Hajnalka; Géczi, László; Vasas, Gábor; Gonda, Sándor (Frontiers in Plant Science, 2022)
The plant microbiome is an increasingly intensive research area, with significance in agriculture, general plant health, and production of bioactive natural products. Correlations between the fungal endophytic communities and plant chemistry can provide insight into these interactions, and suggest key contributors on both the chemical and fungal side. In this study, roots of various horseradish (Armoracia rusticana) accessions grown under the same conditions were sampled in two consecutive years and chemically characterized using a quality controlled, untargeted metabolomics approach by LC-ESI-MS/MS. Sinigrin, gluconasturtiin, glucoiberin, and glucobrassicin were also quantified. Thereafter, a subset of roots from eight accessions (n = 64) with considerable chemical variability was assessed for their endophytic fungal community, using an ITS2 amplicon-based metagenomic approach using a custom primer with high coverage on fungi, but no amplification of host internal transcribed spacer (ITS). A set of 335 chemical features, including putatively identified flavonoids, phospholipids, peptides, amino acid derivatives, indolic phytoalexins, a glucosinolate, and a glucosinolate downstream product was detected. Major taxa in horseradish roots belonged to Cantharellales, Glomerellales, Hypocreales, Pleosporales, Saccharomycetales, and Sordariales. Most abundant genera included typical endophytes such as Plectosphaerella, Thanatephorus, Podospora, Monosporascus, Exophiala, and Setophoma. A surprising dominance of single taxa was observed for many samples. In summary, 35.23% of reads of the plant endophytic fungal microbiome correlated with changes in the plant metabolome. While the concentration of flavonoid kaempferol glycosides positively correlated with the abundance of many fungal strains, many compounds showed negative correlations with fungi including indolic phytoalexins, a putative glucosinolate but not major glucosinolates and a glutathione isothiocyanate adduct. The latter is likely an in vivo glucosinolate decomposition product important in fungal arrest. Our results show the potency of the untargeted metabolomics approach in deciphering plant–microbe interactions and depicts a complex array of various metabolite classes in shaping the endophytic fungal community.